Antitrust and Unfair Competition - Fadillah Ramadhani Siregar; Nikmah Dalimunthe (LPPM UIKA Bogor, 2023)
This study aims to get to know more about Antimonopoly and Unfair Competition, The current busyness of business activities does not escape the presence of rivals. Competition can encourage people to break the law in pursuit of maximum profit. Even so, they engage in an unfair form of competition. This unhealthy business competition harms society as a whole. Competition is fierce in today's business operations throughout Indonesia and other countries. Although the regulation of unfair competition based on Article 1365 of the Civil Code concerning acts contrary to the law and Article 382 bis of the Criminal Code before Law No. 5 was passed in 1999, the provision no longer applies. With the rapid development of the business sector in Indonesia, both the industrial and service sectors are becoming increasingly competitive. This is something that should be seen as a good thing, as it will spur entrepreneurs in this field to work harder than ever to provide customers with the best products and services. This article examines the factors that influence antitrust and unfair business competition, including globalization, competition, business owners, and a literature review on strategic management. The findings of this article's literature review are: First, the effect of economic globalization on antitrust and unfair business competition; two, the impact of unfair business competition; and third, the influence of business owners on antitrust and unfair competition.